Relative area measurement of maxillary sinus by computed tomography - OLIVEIRA,Ronaldo Andrade Figueiredo de (2014)
OBJECTIVE: To evaluate the relative area of the maxillary sinus in edentulous posterior maxilla with regard to linear area, bone septa and sinus pathologies. METHODS: A retrospective longitudinal study was conducted of tomographic exams in 60 individuals between 35 and 75 years of age, with the inclusion criteria being the uni- or bilateral edentulous posterior maxilla. Measurements were taken by the program in 101 maxillary sinuses. The horizontal and vertical measurements of each sinus were multiplied and resulted in a linear area in mm2. RESULTS: Of the 101 maxillary sinuses evaluated, 14 presented sinus pathologies (13.86%) and 22 (21.78%) with bone septa. The mean mesio distal distance was 38.4 mm (p ≤ 0.05), mean height 34. 5 mm (p ≤ 0.05) and mean linear area of 1335.88 mm² (p = 0.05). The Student's-t and analysis of variance (ANOVA) tests were applied for statistical analysis There were no statistically significant difference in the height and width of the edentulous maxillary sinuses between genders, but there was a variation in the linear area and the finding of the presence of bone septa and sinus pathologies. CONCLUSION: The conclusion of this study corroborates those of previous study about the need for imaging exams with the purpose of obtaining information about the dimensions of the maxillary sinus, as guidance with regard to the quantity of graft material, choice of donor region, and presence of septa. These data serve as guidance in the sinus lift technique and the presence of sinus pathologies, which involve treatment before bone graft surgeries.